2020
DOI: 10.1016/j.jccase.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction in young newbie bodybuilder using multiple steroid and protein supplements

Abstract: Coronary artery disease is one of the major reasons for all deaths worldwide and there has been a persistent rise of young myocardial infarction (MI) in past years [1]. The most common etiology for young MI accounts for lifestyle modification which includes sedentary life style, change in dietary habits, stressful and long working hours, strong family history, smoking, and development of other comorbid conditions such as diabetes and hypertension at an early age [2]. In recent times, there has been an upward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Bodybuilders often consume substantial quantities of dietary protein (1.9–4.3 g/kg body mass/day for men, 0.8–2.8 g/kg/day for women) [ 97 ], which exceeds recommendations for strength-trained athletes (1.4–2.0 g/kg/day) [ 98 100 ]. Some individuals may consume even greater amounts, as exemplified in a case report of a novice bodybuilder who consumed 750 g of protein per day [ 101 ]. The unique protein requirements for elite bodybuilders have not been studied, so it is unclear if such high protein intake is excessive or necessary for success [ 102 ].…”
Section: Potential Other Health Risks For Bodybuildersmentioning
confidence: 99%
See 2 more Smart Citations
“…Bodybuilders often consume substantial quantities of dietary protein (1.9–4.3 g/kg body mass/day for men, 0.8–2.8 g/kg/day for women) [ 97 ], which exceeds recommendations for strength-trained athletes (1.4–2.0 g/kg/day) [ 98 100 ]. Some individuals may consume even greater amounts, as exemplified in a case report of a novice bodybuilder who consumed 750 g of protein per day [ 101 ]. The unique protein requirements for elite bodybuilders have not been studied, so it is unclear if such high protein intake is excessive or necessary for success [ 102 ].…”
Section: Potential Other Health Risks For Bodybuildersmentioning
confidence: 99%
“…However, it is difficult to determine if any one factor is causative. This is epitomized by a case report which describes myocardial infarction in a 26-year-old male novice bodybuilder [ 101 ]. The patient began bodybuilding training 2 months earlier, but was training 4 h per day, consuming 500 g of whey protein per day in addition to 250 g of dietary protein, while also taking an appetite suppressant (and lost 6 kg body mass in the previous 2 months), branched chain amino acids supplement, and a mixture of anabolic steroids [ 101 ].…”
Section: Challenges Of Identifying Primary Risk Factors In Bodybuildersmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of individuals using anabolic steroids are not associated with professional sports. They take anabolic steroids to enhance physical attractiveness [50,51]. The average age of steroid users is around 30 years old.…”
Section: Induced By Anabolic Steroidsmentioning
confidence: 99%
“…The use of anabolic steroids increases the risk of SCD in athletes by 6 to 20 times [45]. A few cases of MI associated with the use of anabolic steroids in athletes have been reported [44,45,[49][50][51][52][53][54][55]. It has been shown that testosterone therapy for 90 days can increase the risk of MI [54].…”
Section: Induced By Anabolic Steroidsmentioning
confidence: 99%